Complex assembly, crystallization and preliminary X‐ray crystallographic analysis of the bovine CD8αα–BoLA‐2*02201 complex. Issue 6 (1st June 2014) - Wang, Zhenbao; Chen, Rong; Tariq, Mansoor; Jiang, Bo; Chen, Zhaosan; Xia, Chun
<x xml:space="preserve">Abstract</x> In order to clarify the structural characteristics of the bovine MHC class I molecule (BoLA‐I) complexed with CD8αα (CD8αα–BoLA‐I), bovine CD8αα, BoLA‐I (BoLA‐2*02201) and β2m were expressed and purified, and were then assembled with a peptide derived from Foot‐and‐mouth disease virus (FMDV‐VP1YY9) and crystallized. The crystal diffracted to 1.7 Å resolution and belonged to space group P21, with unit‐cell parameters a = 53.9, b = 103.8, c = 61.8 Å, α = γ = 90, β = 96°. The asymmetric unit contained one complex, with a Matthews coefficient of 2.41 Å3 Da−1 and a solvent content of 48.9%. The rotation‐function Z‐score and translation‐function Z‐score for molecular replacement were 3.4 and 8.9, respectively. In addition, SDS–PAGE analysis of CD8αα–BoLA‐I crystals showed three bands corresponding to the molecular weights of BoLA‐I heavy chain, β2m and CD8α. The structure of the CD8αα–BoLA‐I complex should be helpful in obtaining insight into the interaction between bovine CD8αα and MHC class I molecules. Structure determination of BoLA‐2*02201–FMDV‐VP1YY9 will be useful in the design of vaccines for foot‐and‐mouth disease.